Mechanism of Buying and Selling in Islamic Finance: Paradigm Transformation in Modern Financial Practices - Pramesti, Angeline Wita (Business Finance Analyst Co., 2024)
This study investigates the mechanism of buying and selling in Islamic finance with a focus on the practice of murabahah in the context of Sharia microfinance institutions in Indonesia. The aim of this study is to analyze the implementation of Islamic accounting in murabahah financing based on PSAK No. 102 at Baitul Mal wat Tamwil (BMT) in Jepara Regency. The methodology used in this research is descriptive and comparative analysis of the implementation of Islamic accounting at BMTs that are members of the NU BMT Association in Jepara Regency. Data were collected through interviews, observations, and document analysis. The results show that although some aspects have met the standards of PSAK 102, the implementation of Islamic accounting in murabahah financing at several BMTs is still not fully compliant with these standards. This is mainly related to the recognition, measurement, presentation, and disclosure of murabahah transactions and their compliance with Sharia principles.